Utilization of ULTIF games to improve cognitive abilities of children aged 5-6 years - Tampubolon, Elisabeth; Ervin Nurul Affrida (Tunas Siliwangi, 2025)
It is important for educators and parents to understand children's cognitive development using a needs-based approach that will help ensure children have the opportunity to develop optimally througbstimulation. Proper stimulation can help children develop optimally.mTheopurpose ofpthis studykwas tomdetermine thembenefits of ULTIF gamesoto improvexchildren's cognitive abilities. Thekresearch methodoused was experimental research. Datapcollection using documentation, performance tests and participatory observations analyzedgusing thekt test. Thekpre-test scoreowas 2.03 andkthe post-testkscore was 2.48 so thatzthere was ankincrease inpchildren's cognitivekdevelopment to develop very well. The results of the data analysis showed thatmthe t-count value of 23 was greaterkthan thekt-table of 1.76 withka significanceklevel of 0.05 with N = 15. This proves that the working hypothesis (H) which states that there is an effect of ULTIF games onkthe cognitive abilities ofkchildren agedk5-6 years.